A Study of Entrepreneurial Characteristics and Entrepreneurial Intention among Electrical and Electronic Engineering Students - Azizan, Anim Zalina; Lim, Chi Chuan (Research in Management of Technology and Business, 2023)
Entrepreneurship is flourishing all over the world. It promotes economic growth and development of a country. This is important for job creation, innovation and growth. Therefore, it is the engine that drives the national economy. The problem of unemployment among college graduates is of great concern to policy makers and academics. The first objective of this study was to determine the level of entrepreneurial characteristics of electrical and electronic engineering students. The second objective was to determine the level of entrepreneurial intention among electrical and electronic engineering students. The third objective of the study was to determine the relationship between entrepreneurial characteristics and entrepreneurial intention among electrical and electronic engineering students at UTHM. The scope of this study is limited to the electrical and electronic engineering students at UTHM. This study uses the quantitative research method of questionnaire to collect data, and the data sources include primary and secondary data. To analyze the collected data, this study uses descriptive analysis and correlation analysis. The main finding of this study is that entrepreneurial characteristics have a significant positive relationship with entrepreneurial intention. The scope of this study is limited, so it is suggested for future research to expand the scope of the study.